Efektivitas Penggunaan Media Pembelajaran Video Animasi Terhadap Peningkatan Hasil Belajar Siswa Pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) - Egi Liyana, Khaila (Trigonometri: Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
The aim of this research is to determine the application of animated video learning media to improve mathematics learning outcomes in two-variable linear equation systems (SPLDV). As an innovation in mathematics learning at junior high school (SMP) level, this research discusses the effectiveness of using animated video learning media in improving student learning outcomes. The design used in the research is a literature review, articles are collected using search engines such as Google Scholar, Publish or Phiris and Open Read. The criteria for articles used are those published in 2019-2024. Based on 15 articles collected, the results were obtained that the use of animated video learning media can be used to improve student learning outcomes in two-variable linear equation systems.